Technology of projecting pedagogical model of information system based on fractals - Beknazarova, Saida; Qayumova, Gulshan; Boymurodov, Bobur (AIP conference proceedings, 2024)
The world scale education in the field of fractal pedagogy such a creative approach to practice wide application reach directions efficient scientific studies take is going Advanced in this foreign experiences based on future experts of fractal pedagogy in preparation principles supporting teaching separately importance occupation is enough The main links of the educational process are the teacher, the student, the subject and the applied methodology. It is necessary to emphasize that the skill of teaching science depends on the teacher. It is an important factor that the tools used by the teacher and the knowledge base of his subject meet modern requirements. Because the specialty is considered as a set of knowledge in the special field of information technologies, new technologies, tools, software and so on are improved every day. With these processes, there is a need for a fractal growth of the teacher’s professional skills. On the other hand, students should have the basic understanding of the subjects, be aware of the latest updated knowledge, be able to apply the acquired knowledge in their future professional life, and learn new information and developments. and the development of such is described as a fractal representation of fractal harmony. In this regard, it is important to monitor these processes and offer effective ways to evaluate and manage the activity of teachers and students in the educational process.